Comparative efficacy of muscle energy technique and Bowen technique on hamstrings muscle tightness in chronic low back pain patients - Batool, Kishwar; Mehmood, Mariam; Jafar, Muneeb; Gull, Maham (Pakistan journal of medical sciences, 2024)
To compare the effects of the Muscle Energy Technique (MET) and the Bowen Technique on hamstring muscle tightness in chronic low back pain (CLBP) patients. A randomized clinical trial (RCT) designed study in which 62 participants were recruited through the purposive sampling technique were divided into two groups by the lottery method. Subjects who had pain for more than six months in the back and hamstring tightness were included. The duration of the study was four months from February to May 2023 conducted at Madinah Teaching Hospital Faisalabad. Subjects in Group-A were given the Bowen technique, whereas subjects in Group-B were given the MET. Numeric pain rating scale (NPRS), Oswestry disability index (ODI), and active knee extension (AKE) tests were used for measurements of outcomes. Intra-group comparison by using Friedman test revealed that both Group-A & B subject's pain were reduced (P<0.000), their tightness in back thigh muscles were significantly reduced (P<0.000) and functional activities of subjects were also improved (P<0.000). Mann Whitney test was used to determine the between group comparison. P-value ≤ 0.05 was considered as significant. Inter Group-Analysis revealed that there was no statistically significant difference between effects of Bowen technique & MET on pain, hamstring tightness and disability as both techniques improved pain, flexibility & disability. This study revealed that both groups treated by MET and Bowen Technique had significantly reduced pain, improved flexibility of back thigh muscle and reduced functional disability.